Studi Komparatif Hasil UKBI Mahasiswa Jurusan Bahasa Indonesia Perguruan Tinggi Negeri dan Swasta di Jawa Timur - Tri Winiasih (Madah: Jurnal Bahasa dan Sastra, 2018)
This research aims to describe students’ Indonesian language skills at private and state universities in East Java. The issues discussed are the comparison of the Section I (Listening), Section II (Grammar), Section III (Reading), and the overall score of Indonesian language proficiency. This is a descriptive quantitative research. The data were obtained from the report results UKBI of 3 state universities and 3 private universities in East Java which have  a major in Indonesian language education and make UKBI as a measuring tool to know the language skills of students. The results show, based on the score of UKBI, the average score of section I, II, III, and UKBI scores on public university students is higher than that of private universities. Based on the predicate of UKBI, the average score of Indonesian university students in private and state universities is on the same predicate, which is superior.